ANALISIS TRANSFORMASI STRUKTUR EKONOMI DAN PERUBAHAN PENYERAPAN TENAGA KERJA DI INDONESIA 2002 – 2019 - Arif Zulkarnain; Harlen Harlen; Yusni Maulida (Program Studi Pendidikan Ekonomi Universitas Riau, 2021)
Economic transformation is an important precondition for bringing Indonesia into the group of high-income countries by 2045. The process of transforming the economic structure is actually shown not only in the decreasing proportion of the primary sector which is replaced by the secondary and tertiary sectors in the formation of GDP or GRDP but also focuses on the use of production factors, one of which is labor. This study aims to analyze the process of transforming the economic structure and changes in the proportion of workers in Indonesia and also to see the effect of economic growth and per capita income on the transformation of the economic structure and changes in the proportion of workers in Indonesia. The analysis technique used is the path analysis model which is used to analyze the direct and indirect effects of the independent variable and the dependent variable. Based on the results of the research conducted, economic growth and per capita income have a negative and significant effect, both directly on the proportion of labor and indirectly through the transformation of the economic structure. This shows that the existence of economic growth and an increase in per capita income affects or is followed by a decrease in the dominance of the primary sector (agriculture) and an increase in the dominance of the non-primary sector, namely the industrial and service sectors, both in the transformation of the economic structure and in changes in the proportion of labor.